1989
DOI: 10.1111/j.1365-2990.1989.tb01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Experimental Allergic Neuritis in Lewis Rats

Abstract: An experimental chronic relapsing demyelinating neuropathy was produced by immunizing adult Lewis rats with bovine myelin in low (2.5 mg) and high (5 mg) doses, with and without Mycobacterium tuberculosis in the adjuvant. Each regime produced a similar disease course: acute severe hind limb weakness was followed by apparent recovery and then reappearance of mild neurological deficit with occasional spontaneous exacerbations. The partially recovered animals were relatively resistant to reimmunization with myeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 17 publications
(13 reference statements)
0
9
0
2
Order By: Relevance
“…Brosnan et al (1984) found that 30% of male Lewis rats developed chronic disease after BIR myelin-induced EAN. Adam et al (1989) found that one of nine Lewis rats inoculated with 2.5 mg and eight of nine rats inoculated with 5.0 mg myelin developed an early relapse of EAN. In-creased incidence of relapses with higher doses of inoculum has also been shown by Harvey et al (1987) in EAN in rabbits.…”
Section: Discussionmentioning
confidence: 94%
“…Brosnan et al (1984) found that 30% of male Lewis rats developed chronic disease after BIR myelin-induced EAN. Adam et al (1989) found that one of nine Lewis rats inoculated with 2.5 mg and eight of nine rats inoculated with 5.0 mg myelin developed an early relapse of EAN. In-creased incidence of relapses with higher doses of inoculum has also been shown by Harvey et al (1987) in EAN in rabbits.…”
Section: Discussionmentioning
confidence: 94%
“…Demyelinative changes in both peripheral nerves and spinal nerve roots have also been reported in hypertrophic hereditary motor and sensory neuropathy, 4 protein zero-deficient mice, 9,26 peripheral myelin protein-22 deficient mice, 40 Trembler mice, 2 and Trembler-J mice 13 and in animal models of inflammatory demyelinating neuropathy. 1,14,17,24,38,39 In 2 mice with POEMS, which is a monoclonal plasma cell disorder characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M), and skin changes (S), spinal nerve roots and sural nerves showed the same pathologic changes of demyelination, remyelination, and inflammatory cell infiltration, 42,47 and in 3 cases of diabetic neuropathy, there was severe loss of both large and small MF in sural nerves while segmental demyelination and remyelination was the main finding in both dorsal and ventral spinal roots. 32 Distal intramuscular and subcutaneous MF have rarely been examined in demyelinating peripheral neuropathies, although skin biopsy has been used in the diagnosis of disorders involving unmyelinated 21 and myelinated 11,23,25 fiber disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Hinweise kommen auch vom Tiermodell, der experimentellen autoimmunen Neuritis (EAN), einem akut monophasisch verlaufenden Modell des Guillain-Barré-Syndroms,das manchmal bei Ratten und insbesondere auch bei Kaninchen einen chronisch schubförmigen Verlauf nehmen kann [32,2]. In diesem Tiermodell lassen sich auf morphologischer Ebene deutliche Ähnlichkeiten zur humanen Form der CIDP finden: Zeichen chronischer Entzündung mit zellulären Infiltraten,Ödem und Schwann-Zell-Proliferation mit Zwiebelschalenbildung.…”
Section: Pathogeneseunclassified
“…Das gute Ansprechen betroffener Patienten auf eine Plasmaseparation deutet auf eine Beteiligung des humoralen Immunsystems hin [2,98]. Unlängst konnte durch den Transfer von Serum betroffener Patienten gezeigt werden, dass sich die elektrophysiologischen und pathologischen Charakteristika der Erkrankung auf Tiere übertragen lassen [111].…”
Section: Durch Serumtransfer Ist Die Erkrankung üBertragbarunclassified